HIV associated neurocognitive disorders - Li Zhou; Nitin K. Saksena (MDPI AG, 2013)
Human immunodeficiency virus type 1 is associated with the development of neurocognitive disorders in many infected individuals, including a broad spectrum of motor impairments and cognitive deficits. Despite extensive research, the pathogenesis of HIV-associated neurocognitive disorders (HAND) is still not clear. This review provides a comprehensive view of HAND, including HIV neuroinvasion, HAND diagnosis and different level of disturbances, influence of highly-active antiretroviral therapy to HIV-associated dementia (HAD), possible pathogenesis of HAD, etc. Together, this review will give a thorough and clear understanding of HAND, especially HAD, which will be vital for future research, diagnosis and treatment.